HLA alleles in renal transplant recipients with nonmelanoma skin cancer in southeastern Brazil - Clarissa Schmidt Rogel; Fabiana Covolo de Souza-Santana; Elaine Valim Camarinha Marcos; Marilia Marufuji Ogawa; Geovana Basso; Jane Tomimori (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Renal transplant recipients are submitted to immunosuppression to avoid graft rejection, which makes them susceptible to various conditions. Furthermore, these individuals present malignant tumors more frequently than the general population, including nonmelanoma skin cancer. The individual genetic basis that acts in the pathogenesis of cutaneous cancer may present a protection or susceptibility factor for disease development. One of these factors is the HLA complex. Objective: To investigate HLA alleles association to the occurrence of nonmelanoma skin cancer in renal transplant recipients from São Paulo State. Methods: A total of 213 patients (93 renal transplant recipients with nonmelanoma skin cancer and 120 renal transplant recipients without nonmelanoma skin cancer) were evaluated by retrospective and cross-sectional study. Epidemiological, clinical and HLA typing data were found in databases. HLA class I (A, B) and class II (DR) alleles were compared to establish their association with nonmelanoma skin cancer. Results: Comparing renal transplant recipients with and without nonmelanoma skin cancer, the HLA-B*13 allele was associated with higher risk of developing nonmelanoma skin cancer while B*45 and B*50 alleles were associated with protection. Study limitations: The HLA A, B and DR alleles identification for the kidney transplantation routine is done by low and medium resolution techniques that do not allow discrimination of specific alleles. Conclusion: The involvement of HLA alleles in nonmelanoma skin cancer in renal transplant recipients was confirmed in this study. Renal transplant recipients with HLA-B*13 showed higher risk for developing a skin cancer (OR= 7.29) and should be monitored for a long period of time after transplantation.